Fiber-continuous panel–pillar structure in insect cuticle and biomimetic research. (5th December 2015) - Chen, Bin; Yin, Dagang; Ye, Wei; Lin, Shiyun; Fan, Jinghong; Gou, Jihua
Abstract: Scanning electron microscope (SEM) observation shows that the cuticle of Dorcus titanus is a kind of natural sandwich structure consisting of upper and lower panels and middle pillars. The observation also shows that the material of the sandwich structure is a biocomposite consisting of chitin-fiber layers and sclerous-protein matrix. More careful observation shows that the fiber layers in the sandwich structure continuously join the panels and the pillars to form a fiber-continuous panel–pillar sandwich structure. The strength of the fiber-continuous panel–pillar structure is investigated and compared with that of the non-fiber-continuous panel–pillar structure based on their representative models. It is shown that the fiber-continuous panel–pillar structure has higher ultimate strength compared to that of the non-fiber-continuous panel–pillar structure. Based on the observations and analyses, the fiber-continuous panel–pillar structure is biomimetically fabricated with a special mould and process. The ultimate strength of the structure is tested and compared with that of the non-fiber-continuous panel–pillar structure. It is indicated that the ultimate strength of the fiber-continuous panel–pillar structure is distinctly larger than that of the non-fiber-continuous panel–pillar structure. Graphical abstract: Scanning electron microscope (SEM) observation shows that the cuticle of Dorcus titanus is a kind of natural sandwich structure consisting of upper and lower panels and middle pillars. The fiber layers in the sandwich structure continuously join the panels and the pillars to form a fiber-continuous panel–pillar sandwich structure. Model analyses indicate that the fiber-continuous panel–pillar structure has higher ultimate strength compared to that of the non-fiber-continuous panel–pillar structure. The composite with the fiber-continuous panel–pillar structure is biomimetically fabricated. The ultimate strength of the structure is tested and compared with that of the non-fiber-continuous panel–pillar structure. It is denoted that the ultimate strength of the fiber-continuous panel–pillar structure is distinctly higher than that of the non-fiber-continuous panel–pillar structure. Highlights: There is a fiber-continuous panel–pillar structure (FCPPS) in insect cuticle. The ultimate strength of FCPPS is theoretically and experimentally investigated. The ultimate strength of FCPPS is distinctly higher than that of non-FCPPS.